Wave packet dynamics in periodically kicked nonlinear systems. (11th July 2017) - Yu, Yan; Gao, Yi; Tong, Peiqing
Abstract: We investigate the dynamics of a wave packet in a periodically kicked nonlinear Aubry–André (AA) model when the initial state is localized at a single lattice site. We found that, beside the nonlinearity strength β and the strength (phase) of the quasiperiodic potential λ ( θ ), the kicking period T can also influence the dynamical evolution of the wave packet. Especially when T, β ≪ 1, the periodically kicked nonlinear AA model can be reduced to a static nonlinear AA model with a rescaled nonlinearity strength β / T .